Uncertainty evaluation for in flight radiometric calibration of earth observation sensors - Cibele Teixeira Pinto (2016)
The absolute radiometric calibration is a prerequisite for creating high-quality science data, and consequently, higher-level Earth observation sensors products. The radiometric calibration uncertainty is the key that describes the reliability of calibration results. The main objective of this present work was to develop a method to evaluate the uncertainties inherent in the in-flight absolute radiometric calibration of Earth observation sensors. The methodology developed and tested confirms the hypothesis that the method proposed here is compatible and comparable with other methods practiced by the international science community of satellite radiometric calibration. The uncertainties were determined for two methods of absolute radiometric calibration: reflectance based approach and cross-calibration method. The reflectance-based approach was performed using four different reference surfaces: (a) west part of the Bahia State, Brazil; (b) Atacama Desert, Chile; (c) Algodones Dunes, USA; and (d) South Dakota State University (SDSU) site, USA. Regarding the reflectance-based approach, the main sources of uncertainty are: (a) the instruments used for the reference surface characterization; (b) atmosphere characterization parameters; (c) surface reflectance factor; and (d) radiative transfer code (MODTRAN). The spectroradiometer instrumental uncertainties in laboratory were lower than 1%. The reference panel relative uncertainties were less than 0.25%. The columnar water vapor was derived from the spectral band of the solar photometer centered on 940 nm with an uncertainty lower than 5%. The aerosol optical depth relative uncertainties ranged from 2 12% in Brazil, 1 5% in Chile, 1-11% in Algodones Dunes and less than 1.2% in SDSU site. The most important information related to the reflectance based method is the retrieved surface reflectance factor at the time of sensor overpass the site measured in field. The relative uncertainty of the Algodones Dunes and Atacama Desert reflectance factor was lower than 5%; and the relative uncertainty of Brazil and SDSU reflectance factor ranged from 3% to 10%. The second major source of uncertainty was the accuracy of MODTRAN (2%). The final uncertainty of the TOA radiance predicted by MODTRAN in Brazil and in SDSU site was lower than 10%. The final uncertainty of the TOA radiance predicted by MODTRAN in Atacama Desert and in Algodones Dunes site was lower than 5.5%. These values are the overall total uncertainty of the reflectance based method in the spectral range of 350 to 2400 nm. The cross calibration between both MUX and WFI on-board CBERS 4 and the OLI on board Landsat-8 was performed using the Libya-4 and Atacama Desert sites. During the cross calibration it is necessary to correct the intrinsic offsets between two sensors caused by Spectral Response Function (SRF) mismatches using a spectral band adjustment factor (SBAF). Thus, one of the sources of uncertainty in the cross calibration is the SBAF, which depend on the uncertainty of the target spectral profile and the SRF uncertainty of the two sensors. Here, the SBAF was estimated with an uncertainty lower than 2%. The overall total uncertainty achieved here with cross calibration method using the Libya-4 and Atacama Desert sites was less than 6.5%. The dominant source of uncertainty in cross calibration is the uncertainty associated with the sensor selected as reference. The OLI produces data calibrated to an uncertainty of less than 5% in terms of radiance. Brazil now has a quantitative indication of the quality of the absolute calibration final results. In addition, the country now has autonomy and reliability in the data provided by sensors of national Earth observation program.